Violência simbólica contra educandos transmitida historicamente pela cultura dominante - Lima Neto, Francisco De Paiva [UNESP]; Leão, Andreza Marques de Castro [UNESP] (My University, 2013)
The aim of this study is to conduct a reflective analysis of violence symbolic in the light of the specific case of ideology. For its realization as we starting point the participant observation in classrooms of elementary school. In this process selected two cases (from many observed) that have become emblematic in the production of this work, which brought elements of evident symbolic violence experienced by students. The schoolis part of a social system and ideological and historically constructed in its place there are many cases of students victims of this violence, which reveals the need for this issue to receive the appropriate attention. Remember that you need to understand the deeper aspects of violence practiced on a symbolic way which creates a culture that camouflages violent ideology behind.

O intuito do presente estudo é realizar uma análise reflexiva da violência simbólica à luz do caso específico da ideologia. Para sua realização, tivemos como ponto de partida a observação participante em salas de aula do Ensino Fundamental. Nesse processo, selecionamos dois casos (dos muitos observados) que se tornaram emblemáticos na produção deste trabalho, os quais traziam elementos evidentes da violência simbólica sofrida pelos alunos. A escola é parte de um sistema social e ideológico construído historicamente e, em seu espaço, há muitos casos de alunos vítimas dessa violência, o que desvela a necessidade de este assunto receber a atenção devida. Vale lembrar que é preciso entender aspectos mais profundos da violência praticada de maneira simbólica que gera uma cultura violenta que camufla a ideologia que está por trás.
Symbolic violence against learners historically transmitted by dominant culture
Keywords: Symbolic violence; Ideology; School; Power relation; Authoritarian culture; Violência simbólica; Ideologia; Escola; Relação de poder; Cultura autoritária